2007
DOI: 10.1165/rcmb.2006-0331tr
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heme Oxygenase-1 in Pulmonary Disease

Abstract: Heme oxygenase (HO)-1, the inducible isoform of heme oxygenase, is a cytoprotective enzyme that plays a central role in the defense against oxidative and inflammatory insults in the lung. HO-1 catalyzes the degradation of heme, a potent oxidant, into biliverdin, iron, and carbon monoxide (CO). These downstream products of heme catabolism have recently been found to mediate the antioxidant, antiapoptotic, antiproliferative, vasodilatory, and anti-inflammatory properties of HO-1. Although absence of HO-1 is rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 94 publications
5
170
0
3
Order By: Relevance
“…HO-1 is a rate-limiting anti-inflammatory/antiapoptotic enzyme that catalyzes the conversion of heme into equimolar quantities of biliverdin (further reduced to bilirubin through biliverdin reductase), iron, and carbon monoxide (46). Animal studies have demonstrated that HO-1 plays a critical protective role in several different lung diseases, including ARDS, pulmonary hypertension, asthma, chronic obstructive pulmonary disease (COPD), and hyperoxic lung injury (13). In vivo, exogeneous administration of HO-1 to rats via a recombinant adenovirus significantly attenuated hyperoxic lung injury.…”
Section: L651mentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 is a rate-limiting anti-inflammatory/antiapoptotic enzyme that catalyzes the conversion of heme into equimolar quantities of biliverdin (further reduced to bilirubin through biliverdin reductase), iron, and carbon monoxide (46). Animal studies have demonstrated that HO-1 plays a critical protective role in several different lung diseases, including ARDS, pulmonary hypertension, asthma, chronic obstructive pulmonary disease (COPD), and hyperoxic lung injury (13). In vivo, exogeneous administration of HO-1 to rats via a recombinant adenovirus significantly attenuated hyperoxic lung injury.…”
Section: L651mentioning
confidence: 99%
“…HO-1, a heme-degrading enzyme, is highly induced by oxidative stress and plays a critical role in defending the lung against inflammatory and oxidant-induced cellular and tissue injury (13,32). HO-1 is induced by a number of signaling pathways and transcription factors (1,41).…”
mentioning
confidence: 99%
“…12 Airway smooth muscle contractility, which can be increased through ROS formation, is inhibited by HO-1 induction. 13 Moreover, the 5Ј-untranslated region of the human HO-1 gene contains many stress-activated response elements, such as antioxidant response elements.…”
Section: The P47mentioning
confidence: 99%
“…HO-1 is the inducible isoform of haem oxygenase and catalyses the degradation of haem, a potent oxidant, to generate biliverdin, iron and carbon monoxide [13]. Biliverdin is converted to bilirubin, a potent endogenous anti-oxidant, while iron is sequestered by ferritin, leading to an additional anti-oxidant effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…Biliverdin is converted to bilirubin, a potent endogenous anti-oxidant, while iron is sequestered by ferritin, leading to an additional anti-oxidant effect [13]. CO has anti-inflammatory properties [13], suggesting that HO-1 plays a critical role in defending the lung against inflammatory and oxidant-induced cellular and tissue injury and is considered to be a potential therapeutic target in allergic inflammation [14].…”
Section: Introductionmentioning
confidence: 99%